Microfluidic Approach toward Continuous and Ultrafast Synthesis of Metal–Organic Framework Crystals and Hetero Structures in Confined Microdroplets. - Faustini, Marco; Jun Kim; Guan-Young Jeong; Jin Yeong Kim; Hoi Ri Moon; Wha-Seung Ahn; Dong-Pyo Kim (Journal of the American Chemical Society, 2013)
Herein, we report a novel nanoliter dropletbased microfluidic strategy for continuous and ultrafast synthesis of metal-organic framework (MOF) crystals and MOF heterostructures. Representative MOF structures, such as HKUST-1, MOF-5, IRMOF-3, and UiO-66, were synthesized within a few minutes via solvothermal reactions with substantially faster kinetics in comparison to the conventional batch processes. The approach was successfully extended to the preparation of a demanding RuBTC structure that requires high-pressure hydrothermal synthesis conditions. Finally, three different types of core-shell MOF composites, i.e., CoBTC@NiBTC, MOF-5@diCH-MOF-5, and FeO@ ZIF-8, were synthesized by exploiting a unique two-step integrated microfluidic synthesis scheme in a continuous-flow mode. The synthesized MOF crystals were characterized by X-ray diffraction, scanning electron microscopy, and BET surface area measurements. In comparison with bare MOF-5, MOF-5@diCH-MOF-5 showed enhanced structural stability in the presence of moisture, and the catalytic performance of FeO@ZIF-8 was examined using Knoevenagel condensation as a probe reaction. The microfluidic strategy allowed continuous fabrication of high-quality MOF crystals and composites exhibiting distinct morphological characteristics in a time-efficient manner and represents a viable alternative to the time-consuming and multistep MOF synthesis processes.